2006
DOI: 10.1128/jvi.00543-06
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Triggering Receptor Expressed on Myeloid Cells-1 on Human Neutrophils by Marburg and Ebola Viruses

Abstract: Marburg virus (MARV) and Ebola virus (EBOV), members of the viral family

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 46 publications
3
99
0
Order By: Relevance
“…Conversely, the binding of filoviruses to C-type lectin molecules is significantly inhibited by the carbohydrate mannan, which indicates that the binding is due to the interaction between carbohydrate motifs on the surface of host cells and N-linked carbohydrate structures of glycoprotein on the filoviral surface. Recently, we also observed that a class of immunorecognition receptors known as TREMs, which are implicated in the amplification of septic shock and cell activation, might have a crucial early role in the interaction of filoviruses with neutrophils 12 , monocytes and mature DCs.…”
Section: Invariant Natural Killer T Cellmentioning
confidence: 98%
See 1 more Smart Citation
“…Conversely, the binding of filoviruses to C-type lectin molecules is significantly inhibited by the carbohydrate mannan, which indicates that the binding is due to the interaction between carbohydrate motifs on the surface of host cells and N-linked carbohydrate structures of glycoprotein on the filoviral surface. Recently, we also observed that a class of immunorecognition receptors known as TREMs, which are implicated in the amplification of septic shock and cell activation, might have a crucial early role in the interaction of filoviruses with neutrophils 12 , monocytes and mature DCs.…”
Section: Invariant Natural Killer T Cellmentioning
confidence: 98%
“…Viral particles, in turn, are able to trigger polymorphonuclear leukocytes (such as neutrophils) to expel the contents of their preformed granules and enter a state of activation 12 . Such early inflammatory responses are not extraordinary and might even be helpful in shaping normal immune responses 30 , but might also exacerbate an underlying early immune response dysfunction that originates principally in DCs.…”
Section: Box 1 | Filovirus-disease Basicsmentioning
confidence: 99%
“…1 TREM-1 expression is further up-regulated by TLR ligands. Binding of TREM-1 to endogenous ligand(s) expressed on granulocytes and platelets and present in sera of septic patients, [2][3][4] as well as to exogenous ligands on Marburg and Ebola viruses, 5 has been described. The exact nature of TREM-1 ligand(s), however, remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…These included genes that regulate intercellular communication between DC and NK cells, TREM1 signaling, and DC maturation (Table 3). Within the TREM1 pathway, molecules that mediate pathogen recognition and subsequent inflammation (TREM1, NOD2, and TYROBP) (2,22,26) and chemoattractant molecules (MIP-1␣, MCP-1, and MCP-3) had the highest expression in IL1RKO mice among all mouse strains (Fig. 6A).…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have shown that TREM1 amplifies inflammation during bacterial (2) and Ebola virus (22) infections in part through the activation of DAP12 signaling pathways and is linked to increased proinflammatory cytokine secretion and survival of neutrophils and monocytes. Our findings related to the TREM1 pathway at 1 dpi are particularly interesting, given the link between this molecule and the host response to other microbial pathogens.…”
Section: Discussionmentioning
confidence: 99%